Pleasure, quality or status? an analysis of drivers of purchase of fresh pork in China - Mulders, Maartje D. G. H.; Grunert, Klaus G.; Pedersen, Susanne; Brunsø, Karen; Zhou, Yanfeng (Frontiers in Animal Science, 2024)
What are consumers aiming to get when they buy fresh meat? Is it the emotional pleasure, the nutritional quality and functionality, or the status that goes with it? We examine this question for Chinese consumers buying fresh pork. In order to understand the driving forces for pork purchases, we use the concept of perceived value of a product, and distinguish emotional value, quality/performance and social value, together with price/value for money. We look at how perceived value of pork products in China is related to consumers' attitude to these products and to their repeated purchase of these products. In addition, we look at how value perception and its role in determining attitude and purchase behaviour differ between different consumer segments, distinguished based on their shopping behaviour. An online survey was carried out in 5 Chinese 1 st and 2 nd tier cities. Respondents were segmented based on their usage of different ways of shopping for pork using latent class cluster analysis. Relationships between constructs were estimated using PLS. Quality/functional value was the strongest determinant of attitude, but emotional value was both the strongest direct determinant of purchase behavioural and the strongest determinant overall when taking effects mediated by attitude into account. Customer journey segments differed in their pattern of determinants of attitudinal and behavioural loyalty. We conclude that buying fresh meat is, for Chinese consumers, mostly driven by the expected pleasure and to a lesser degree by quality and functional properties like safety and healthiness. The latter do have an impact on consumers' attitude to the product, but less so on their buying behaviour, suggesting that attitude and purchase are driven by different mental processes. We discuss implications for future demand for fresh pork in China.